2011
DOI: 10.1063/1.3601743
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurements of the heats of formation of Fe3Pt, FePt, and FePt3 using differential scanning calorimetry

Abstract: Using differential scanning calorimetry (DSC), the heats of formation of Fe3Pt, FePt, and FePt3 were determined from the reaction of sputter deposited Fe/Pt multilayer thin-films with a periodicity of 200 nm but different overall compositions. Film compositions were measured by energy dispersive x-ray spectrometry. The phases present along the reaction path were identified by x-ray diffraction. For the most Fe-rich phase, namely, Fe3Pt, the measured enthalpy of formation was −9.3 ± 1.3 kJ/mol in a film with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…6c, d, the signal intensity of the images changes drastically with the variation of Fe concentration for both arrays. Transverse relaxivity (r 2 20 Pt 80 (or A1-FePt NPs) due to their higher magnetization (Fig. 6c-f), which demonstrates that FePt intermetallic NPs can be applied as a potential T 2 contrast agent for MRI.…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…6c, d, the signal intensity of the images changes drastically with the variation of Fe concentration for both arrays. Transverse relaxivity (r 2 20 Pt 80 (or A1-FePt NPs) due to their higher magnetization (Fig. 6c-f), which demonstrates that FePt intermetallic NPs can be applied as a potential T 2 contrast agent for MRI.…”
Section: Articlesmentioning
confidence: 99%
“…To date, most studies on FePt intermetallics with tun-able crystal structures are limited to thin films, while the investigation on single-particle magnetism of FePt intermetallics is few [17][18][19][20][21][22]. Liu et al [23] first reported a systemic study on FePt intermetallic NPs prepared by a sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, one should also note that the L1 2 phase is not the 0 K ground state of Fe 3 Pt. Barabash [42] and previous theoretical values (GGA (DTU) [43] and GGA (CMU) [44]). Results computed with the 2 Â 2 Â 2 and 3 Â 3 Â 3 supercells (SC) are given by squares and triangles, respectively.…”
Section: Bain Pathmentioning
confidence: 75%
“…Differential scanning calorimetry (DSC) is widely used in the study of thermal protein denaturation 9. Wang et al34 have reported DSC studies that provided enthalpies of formation of Fe 3 Pt, FePt, and FePt 3 in ordered intermetallic multilayer Fe/Pt films important in magnetic recording media. Stevens et al35 have used the nonclassical method of threshold photoelectron photoion coincidence to determine the enthalpies of formation of the unstable species phenyl, phenylium and of nitrosobenzene and nitrosobenzene ions with ATcT analysis 24…”
Section: Determination Of δFh°298mentioning
confidence: 99%